“Broken” pathways : understanding the licensing experiences of overseas-trained medical doctors in Aotearoa New Zealand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Palmerston North, Aotearoa New Zealand - Thomas-Maude, Johanna (Massey University, 2024)
More than 40% of registered medical doctors in Aotearoa New Zealand received their primary medical qualifications overseas. Within this landscape, the pathways that international medical graduates (IMGs) must follow to achieve professional licensing depend on their background. This research explores IMG experiences of these processes using a capabilities approach to mobility justice, finding that although pathways to registration exist on paper, many are broken, unpredictable, and often unattainable in practice. General registration is available to doctors who completed their primary qualifications, or have worked for a minimum time period, in 24 high-income, Global North countries known as Comparable Health Systems (CHS). Other IMGs must apply for registration by taking a medical knowledge examination from the United Kingdom (U.K.), Australia, Canada, or the United States of America (U.S.A.), demonstrating English language competency, and taking the New Zealand Registration Examination (NZREX), which evaluates context-specific clinical skills. While completing these steps is time-consuming and costly, IMGs on the NZREX pathway are also required to complete two years of supervised work in local hospitals. First year positions, known as Postgraduate Year One (PGY1), are limited and prioritised for New Zealand medical graduates (NZMGs). As a result, a bottleneck has delayed or prevented many of these IMGs, typically originating from Global South countries, from finding PGY1 employment. This research addresses a knowledge gap by exploring the relationship between IMG experiences, professional outcomes, and their designated pathway to registration. An exploratory sequential mixed methods research design was employed, consisting of semi-structured interviews of IMGs (n = 24) and local experts (n = 9), an online questionnaire of IMGs (N = 80), and a document analysis of historical policies, grey literature, and media reports (N = 370), across three phases. The project was framed by a capabilities approach to mobility justice that evolved alongside the research design, data collection, and analysis. This theoretical approach considers what IMGs in Aotearoa New Zealand are able to “be” and “do” as migrant professionals, through four key components known as the 4Ps. The 4Ps comprise professional mobilities and capabilities, (inter)personal mobilities and capabilities, mobilities and capabilities in practice, and mobilities and capabilities power regimes. Combining empirical data with this theoretical lens highlights how medical registration pathways and policies contribute to uneven mobilities and capabilities among IMGs in Aotearoa New Zealand. Injustices are produced through misrecognition and the arbitrary exclusion of individuals who did not train in CHS countries. Such arbitrary exclusions, in turn, produce brain waste, whereby some IMGs already residing in Aotearoa New Zealand were unable to work as doctors, or experienced significant delays in registration, even during the COVID-19 pandemic. This situation is detrimental not only to these IMGs, but also to the chronically under-resourced local medical workforce and, consequently, the broader population in need of healthcare. Furthermore, colonial vestiges can be seen to have contributed to a recurring cycle of policy changes, which have culminated in contemporary licensing policies strongly resembling those from 1905. To create more just pathways for registration for IMGs in Aotearoa New Zealand, this (post)colonial cycle needs to be examined, evaluated, and broken, paving the way for more equitable medical regulation.
Listed in 2024 Dean's List of Exceptional Theses
Keywords: Physicians, Foreign; Certification; Clinical competence; Government policy; Medical laws and legislation; Experiential learning; New Zealand; medical migration; international medical graduates; mobility justice; capabilities; brain waste; postcolonialism; Aotearoa New Zealand; Dean's List of Exceptional Theses; 440403 Labour, migration and development